2007
DOI: 10.1111/j.1600-6143.2006.01585.x
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Wild-Type Transthyretin Deposition after Liver Transplantation Preferentially Occurs onto Myocardium in FAP Patients

Abstract: To elucidate whether progressive wild-type transthyretin (TTR) deposition can actually occur after liver transplantation (LT), amyloid fibrils were investigated in two familial amyloid polyneuropathy patients with TTR Val30Leu variant, who died 1 year after LT. Amyloid fibrils were extracted from cardiac muscles, sciatic nerves and kidney, which were investigated by the immunoprecipitation-mass spectrometry method and liquid chromatographyion trap mass spectrometry analysis. The ratio of wild-type to variant T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(73 citation statements)
references
References 24 publications
2
68
1
2
Order By: Relevance
“…Scintigraphy with 123 I serum amyloid P component showed mobilization of visceral amyloid, namely in the kidney, although mobilization of renal deposits by histology has never been proven (54). Support for de novo amyloid deposition was demonstrated by the type of fibrils extracted from the kidney before OLT (55). The fibrils did not contain obvious WT-TTR; however, after OLT, WT-TTR was evident, in a process similar to that in the heart, although in a less substantial amount.…”
Section: Treatment Of Attrmentioning
confidence: 99%
“…Scintigraphy with 123 I serum amyloid P component showed mobilization of visceral amyloid, namely in the kidney, although mobilization of renal deposits by histology has never been proven (54). Support for de novo amyloid deposition was demonstrated by the type of fibrils extracted from the kidney before OLT (55). The fibrils did not contain obvious WT-TTR; however, after OLT, WT-TTR was evident, in a process similar to that in the heart, although in a less substantial amount.…”
Section: Treatment Of Attrmentioning
confidence: 99%
“…The amount of amyloid deposition in nerve tissues including the entire length of the peripheral nerves, dorsal root and sympathetic ganglia is greater in early-onset patients [40], while in late-onset patients the accumulation of Congo-red-negative but TTR-immunoreactive non-fibrillar protein is abundant in these tissues [17]. This pathologic amyloid-related protein deposition consists of both variant and wild type TTR [41], the latter being predominant in the involved tissues in late-onset patients [17]. These findings indicate that the underlying pathogenetic mechanism of amyloid neuropathy differs between Kodaira et al 17 of 26 both types.…”
Section: Difference In Pathophysiology Between Endemic-versus Non-endmentioning
confidence: 99%
“…Since the source of variant TTR production leading to amyloid fibril is removed at the time of OLT, the accumulation of new amyloid deposits is completely unexpected. Subsequent evaluation of the amyloid deposits has shown that wild-type TTR is present in increased amounts in the heart following OLT [62,63]. Thus, it appears that wild-type TTR can continue to form amyloid deposits, particularly in the heart, in patients with ATTR following OLT.…”
Section: Treatment Of Attrmentioning
confidence: 99%